Sediment contamination by trace elements and the associated ecological and health risk assessment: A case study from a large reservoir (Turkey) - Canpolat, Ozgur; Varol, Memet; Okan, Ozlem Oztekin; Eris, Kursad Kadir (Academic Press Inc Elsevier Science, 2022)
Although Keban Reservoir (KR) is Turkey's the second largest man-made reservoir, limited data are available on the contents of trace elements (TEs) in sediments of the KR. The concentrations of 23 less- and commonlymonitored TEs in the sediments from 49 sites in the reservoir were measured to assess health risks, contamination levels and ecological risks of TEs. Concerning median Enrichment Factor values of TEs, chromium (Cr), strontium (Sr) and nickel (Ni) showed moderate enrichment, while other TEs showed minimal enrichment. Pollution Load Index values ranged from 0.33 to 0.63, indicating no a multi-element contamination case in the study area. Low ecological risk was found at 47 sites, while moderate ecological risk was recorded at two sites. The PEC (probable effect concentration) values were exceeded for Ni and Cr. Although wastewater from leather processing factory partly contributed to Cr enrichment at site 2, all TEs mainly originated from lithogenic sources. Median hazard quotient (HQ) values of zirconium (Zr) and lanthanum (La) for children from sediment ingestion were above the risk threshold of unity (HQ = 4.81 and 1.39) and contributed 62.9% and 18.2% of the total health risk. Such high HQ values of Zr and La have never been reported in the literature. Hazard index values for children exceeded those for adults, indicating that children are more vulnerable to health risks than adults. Carcinogenic risk values of arsenic (As) were within the acceptable limits. Our findings indicated that in a multi-element sediment study, some less-monitored elements such as Zr and La may have an important role in health risk assessment even if they are found in the sediment at low concentrations. Therefore, this study can be a model for future similar studies evaluating the health risks of multi-elements in sediments.
Keywords: Trace elements; Sediments; Pollution indices; Risk assessment